Object tracking in video via particle filter. (2016) - Abdelali, Hamd Ait; Essannouni, Fedwa; Aboutajdine, Driss
In this paper, we present a new method for object tracking. We use an efficient local search scheme based on the probability product kernel using particle filter (PPKPF) to find the image region with a histogram most similar to the histogram of the tracked target. Experimental results verify the effectiveness of this proposed algorithm.